2022
DOI: 10.1021/acsomega.2c01660
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Signatures of Surface-Modified Poly(lactic-co-glycolic acid) Nanoparticles in Differentiated THP-1 Cells Derived with Liquid Chromatography-Mass Spectrometry-based Metabolomics

Abstract: Polymeric nanoparticles (NPs) are widely used in preclinical drug delivery investigations, and some formulations are now in the clinic. However, the detailed effects of many NPs at the subcellular level have not been fully investigated. In this study, we used differentiated THP-1 macrophage cells, as a model, to investigate the metabolic changes associated with the use of poly (lactic- co -glycolic acid) (PLGA) NPs with different surface coating or conjugation chemistries. Liquid chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…49 Similarly, polymeric nanoparticles (NPs) altered metabolic pathways related with glycerophospholipid, sphingolipid, linoleic acid, arginine and proline, and alpha-linolenic acid metabolisms in macrophages. 50 We reported that MWCNTs and graphene oxide upregulated Cer in endothelial cells 29 and human brain organoids, 51 which could be related with the cytotoxicity of the materials to these models. As such, the upregulation of sphingolipids especially by MWCNTs could be related with cardiovascular disease development.…”
Section: Discussionmentioning
confidence: 92%
“…49 Similarly, polymeric nanoparticles (NPs) altered metabolic pathways related with glycerophospholipid, sphingolipid, linoleic acid, arginine and proline, and alpha-linolenic acid metabolisms in macrophages. 50 We reported that MWCNTs and graphene oxide upregulated Cer in endothelial cells 29 and human brain organoids, 51 which could be related with the cytotoxicity of the materials to these models. As such, the upregulation of sphingolipids especially by MWCNTs could be related with cardiovascular disease development.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, they affected cell membrane integrity by reducing levels of PC and phosphatidylethanolamines, which are essential membrane components. On the contrary, PEGylated PLGA NPs showed less disturbance in amino acid metabolism and cell membrane’s glycerophospholipids composition [ 193 ]. A summary of the effect of versatile NPs on various metabolites and metabolic pathways is provided in Table 1 .…”
Section: Nanoparticles-associated Changes In the Cellular Metabolomementioning
confidence: 99%